Peranan Kualitas Produk Dalam Meningkatkan Efektivitas Penjualan Perspektif Ekonomi - Agnes yolanda; Arista khairunnisa; syafri yanto; Dita Afrina (AGHNIYA: Jurnal Perbankan Syari'ah, 2024)
The purpose of this research was describe the role of product quality in increasing the effectiveness of sales from an syariah economic perspective (a case study of the Nova rice store, Padang Tepong Village, Ulumusi District, Empat Lawang Regency). This research was a qualitative descriptive research that describes two aspects of the problem formulation, namely the role of product quality in increasing sales effectiveness and improving product quality in increasing sales effectiveness from a sharia economic perspective. Research data obtained by conducting observations, interviews, and documentation studies. Data analysis techniques were carried out in stages: data collection, data reduction, data presentation, drawing conclusions. The results of the research showed that: (1) Based on the results of the research it covid be concluded that the role of product quality at the Nova rice store, Padang Tepong Village, Ulu Musi District, Empat Lawang Regencycovid increase the effectiveness of sales, this covid be seen from the number of buyers' interest and buyer satisfaction with the quality of the product (rice) in the Nova rice shop, (2) According to an Islamic Economic review, product quality at the Nova rice shop was in accordance with sharia values, maintaining product cleanliness and not selled products that has not been sold for a long time, so that product quality was maintained and of course making products marketed became superior products in accordance with the needs and desires of buyers.